PANCASILA DAN SYARI'AT ISLAM SEBAGAI ASAS-ASAS PEMBENTUKAN QANUN DI NANGGROE ACEH DARUSSALAM (Studi Kasus Peraturan Daerah No. 5 Tahun 2000 Tentang Pelaksanaan Syariat Islam ) - , Delfi Suganda ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia is a unitary state based on the constitution and the law, this makes the implementation and application of constitutional law applies nationwide and there is a central government authority. Aceh is a province that is part of the Republic of Indonesia should implement national laws. Perda No.5 Year 2000 on the implementation of Islamic Shari'ah as a foundation stone in the application of Islamic Shari'ah in Aceh. This obviously makes the application of the two laws in Aceh, the national law and the law in Aceh. Apart from that the area rulemaking process also occurs in the process of formation juridical mistake, this is due to the loading of the Al-Quran and Al-Hadith in the regulatory area. The method of research is empirical-normative that is by conducted the library research and interviews. After conducting interviews with multiple informants and then do some research at the library to collect the data, then the researcher makes an analysis of the data that is found in the field. Pancasila is the source of all law in Indonesia, which is the cornerstone in the implementation and the establishment of national laws and regulations. Pancasila presence makes the appreciation of the local products in Aceh that are special. There is confusion in the application of that law to make Pancasila as the harmonization of the two, between the applicable national law in Aceh and local laws that are Acehnese desire itself. Pancasila as the state philosophy teaches about kindness to all of the existing legal instruments in Indonesia, with the Pancasila as the view state law must be formed based on the wishes of the people who live in the country. Thus clearly, the presence of Pancasila in the establishment of local regulations will create harmonization and legal products are formed not by political interests, but based on public interest requires the establishment of local regulations such as law in the implementation of Islamic Shari'ah.